The effect of Stop X exercises on balance, strength and range of motion of male adolescent football players with dynamic knee valgus - Rahman Hasani Chenari; Ebrahim Mohammad Ali Nasab Firouzjah; Sajad Roshani (Scientific Reports)
Abstract Dynamic valgus of the lower limb is known as a risk factor associated with improper muscle function for many lower limb injuries, especially knee injuries. Stop X exercises has been designed to enhance spatial orientation, prediction, and attention; increase body stability and movement coordination; and teach the appropriate landing techniques. Therefore, the aim of the present study was to investigate the effect of Stop X exercises on the balance, strength and range of motion (ROM) of male adolescent football players with dynamic knee valgus (DKV). Thirty football players with DKV were selected purposefully and were randomly divided into two groups, control (n = 15) and training (n = 15). Stork tests, Y-balance test (YBT), goniometer, and digital dynamometer were used to evaluate static balance, dynamic balance, ROM, and hip abduction and external rotation strength, respectively. Analysis of variance (ANOVA) and dependent t-tests were used to compare the between and within group differences. After 8 weeks of Stop X exercises, values showed significant improvements in hip abduction (p = 0.005) and external rotation (p = 0.001) strength and ROM (p = 0.009), static balance (p = 0.006) and total score of YBT (p = 0.001). The findings of this study suggest that the STOP-X injury prevention program enhances hip abduction and external rotation strength, ROM, as well as static and dynamic balance in adolescent football players with DKV. Therefore, it is recommended that sports trainers incorporate STOP-X training into the regular exercise routines for adolescent football players to leverage these benefits.